MXene-regulated perovskite vertical growth for high-performance solar cells - Wu,C; Fang,W; Cheng,Q; Wan,J; Wen,R; Wang,Y; Song,Y; Li,M (Angewandte Chemie International Edition, 2022)
Defects at the interfaces of perovskite (PVK) thin films are the main factors responsible for instability and low photoelectric conversion efficiency (PCE) of PVK solar cells (PSCs). Here, a SnO2-MXene composite electron transport layer (ETL) is used in PSCs to improve interfacial contact and passivate defects at the SnO2/perovskite interface. The introduced MXene regulates SnO2 dispersion and induces a vertical growth of PVK. The lattice matching of MXene and perovskite suppresses the concentration of interfacial stress, thereby obtaining a perovskite film with low defects. Compared with SnO2-based device, the PCE of SnO2-MXene-based device is improved by 15 % and its short-circuit current is up to 25.07mA cm−2. Furthermore, unencapsulated device maintained about 90 % of its initial efficiency even after 500h of storage at 30–40 % relative humidity in ambient air. The composite ETL strategy provides a route to engineer interfacial passivation between metal halide perovskites and ETLs.